A Union Goes to War: The Victorian State Services Federation in the Great War. (1st May 2017) - Bollard, Robert
Abstract : The Great War saw dramatic growth in the Victorian State Services Federation, the union that covered state public servants and a variety of other public sector workers. The economic and political crisis engendered by the war is revealed, not only in this growth, but in an internal argument (and split) within the Federation over the issue of the Federation's support for Maurice Blackburn in the 1917 state election. The sectarian dimensions of this division are particularly revealing, especially in association with the formation of the Police Association, under the aegis of the Federation, also in 1917. For all that the Federation never resorted to industrial action, beneath the veneer of white collar respectability the radicalisation of a significant section of the working class by the crisis of the war is evident.